Low Influenza Vaccine Effectiveness Against A(H3N2)-Associated Hospitalizations in 2016–2017 and 2017–2018 of the Hospitalized Adult Influenza Vaccine Effectiveness Network (HAIVEN). (3rd November 2020) - Martin, Emily T; Cheng, Caroline; Petrie, Joshua G; Alyanak, Elif; Gaglani, Manjusha; Middleton, Donald B; Ghamande, Shekhar; Silveira, Fernanda P; Murthy, Kempapura; Zimmerman, Richard K; Monto, Arnold S; Trabue, Christopher; et al.
Abstract: Background: The 2016–2017 and 2017–2018 influenza seasons were notable for the high number of hospitalizations for influenza A(H3N2) despite vaccine and circulating strain match. Methods: We evaluated vaccine effectiveness (VE) against hospitalization in the test-negative HAIVEN study. Nasal-throat swabs were tested by quantitative reverse transcription polymerase chain reaction (RT-PCR) for influenza and VE was determined based on odds of vaccination by generalized estimating equations. Vaccine-specific antibody was measured in a subset of enrollees. Results: A total of 6129 adults were enrolled from 10 hospitals. Adjusted VE against A(H3N2) was 22.8% (95% confidence interval [CI], 8.3% to 35.0%), pooled across both years and 49.4% (95% CI, 34.3% to 61.1%) against B/Yamagata. In 2017–2018, the A(H3N2) VE point estimate for the cell-based vaccine was 43.0% (95% CI, −36.3% to 76.1%; 56 vaccine recipients) compared to 24.0% (95% CI, 3.9% to 39.9%) for egg-based vaccines. Among 643 with serology data, hemagglutinin antibodies against the egg-based A(H3N2) vaccine strain were increased in influenza-negative individuals. Conclusions: Low VE for the A/Hong Kong/4801/2014 vaccine virus in both A(H3N2) seasons emphasizes concerns for continued changes in H3N2 antigenic epitopes, including changes that may impact glycosylation and ultimately reduce VE. Abstract : Across 2 years of a prospective, multicenter, test-negative study of influenza vaccine effectiveness in prevention of hospitalization, we found VE of 33.5% against any influenza-associated hospitalization and a low VE of 22.8% for the A/Hong Kong/4801/2014 vaccine strain.